2022
DOI: 10.1002/sd.2439
|View full text |Cite
|
Sign up to set email alerts
|

Green hydrogen partnerships with the Global South. Advancing an energy justice perspective on “tomorrow's oil”

Abstract: Fuel cells and other hydrogen-based technologies are increasingly seen as a key pillar of global decarbonization efforts. A major challenge to be overcome is the future availability of large quantities of affordable green hydrogen to supply the envisioned hydrogen economy. Several industrialized countries have formulated ambitious national hydrogen strategies that rely heavily on importing green hydrogen from other countries, including countries in the Global South that are rich in renewable energy. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…And sustainability was the second most widely disseminated theme by scholars in their respective research related to green hydrogen, being due to the said word is the main one in many scientific subjects (Panah et al, 2022), particularly nowadays in relation to green hydrogen, i.e. in the framework of the improvement of renewable sources, and in this case energy sustainability is strong (Ali et al, 2022), through the change of carbon-based fuels (Genovese,et al, 20200220), through the hydrogen which is progressively verified as a relevant foundation for achieving decarbonization (Lindner, 2022) for renewable energy generation (Zuben, et al, 2022). This is how the third topic most sought after by researchers to publish their respective findings and contributions in relation to green hydrogen, which is anergy, and its relevance is due, therefore, to the production of hydrogen from hydroelectric energy, which is a niche opportunity to lead countries towards sustainable energy solutions and a hydrogen-powered economy (Thapa et al, 2021), thus influencing the decarbonization goals in the world (Raman et al, 2022), and thus corroborating energy development to make it feasible sustainable development (Guarieiro et al, 2022), while simultaneously providing opportunities for expansion into a green hydrogen-based society (LeeTentet al, 2022).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And sustainability was the second most widely disseminated theme by scholars in their respective research related to green hydrogen, being due to the said word is the main one in many scientific subjects (Panah et al, 2022), particularly nowadays in relation to green hydrogen, i.e. in the framework of the improvement of renewable sources, and in this case energy sustainability is strong (Ali et al, 2022), through the change of carbon-based fuels (Genovese,et al, 20200220), through the hydrogen which is progressively verified as a relevant foundation for achieving decarbonization (Lindner, 2022) for renewable energy generation (Zuben, et al, 2022). This is how the third topic most sought after by researchers to publish their respective findings and contributions in relation to green hydrogen, which is anergy, and its relevance is due, therefore, to the production of hydrogen from hydroelectric energy, which is a niche opportunity to lead countries towards sustainable energy solutions and a hydrogen-powered economy (Thapa et al, 2021), thus influencing the decarbonization goals in the world (Raman et al, 2022), and thus corroborating energy development to make it feasible sustainable development (Guarieiro et al, 2022), while simultaneously providing opportunities for expansion into a green hydrogen-based society (LeeTentet al, 2022).…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 99%
“…For hydrogen to play a role in future low-carbon energy systems, it must be demonstrated that it has sufficiently low carbon emissions (Abad & Dodds, 2020;Ali, Bennui, Chowdhury & Techato, 2022). Given the above, it is emphasized that fuel cells and other hydrogen-based technologies are increasingly seen as a key pillar of global decarbonization efforts (Lindner, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of industry partnerships, international collaboration, and the development of standards for hydrogen safety is emphasized in the context of advancing material science for hydrogen energy. These collaborations and standards are crucial for translating research findings into practical applications, ensuring scalability, cost-effectiveness, and alignment with broader energy transition goals (Lindner, 2022;Yan-Mei et al, 2020).…”
Section: Future Prospects and Potentialmentioning
confidence: 99%

Material science in hydrogen energy: A review of global progress and potential

Igberaese clinton festus-ikhuoria,
Nwankwo Constance Obiuto,
Oladiran Kayode Olajiga
et al. 2023
World J. Adv. Res. Rev.
“…Furthermore, there is an increasing body of literature that addresses another blind spot, namely the implications of hydrogen trade for the hydrogen export countries. These studies start from the objective of energy justice and have taken a more critical perspective towards hydrogen partnerships [37][38][39][40]. Müller et al point out that hydrogen partnerships with countries such as Morocco or Namibia risk exacerbating existing inequities rather than leading to a just transition [38].…”
Section: Hydrogen Diplomacymentioning
confidence: 99%